Greener European Agriculture? Evaluating EU Member States’ Transition Efforts to Integrated Pest Management through Their National Action Plans - Florența-Elena Helepciuc; Arpad Todor (Agronomy, 2022)
Integrated pest management (IPM) is among the most promising approaches for transforming today’s agronomical practices toward sustainable and environmentally friendly agriculture. Aiming to become a global environmental leader, in 2009, the European Union (EU) embraced the idea of making IPM practices ubiquitously used by 2014 in all EU Member States (EU MSs). Through Directive 2009/128/EC (the Sustainable Use Directive (SUD), the EU required EU MSs to structure their transformative measures in National Action Plans (NAPs) in a comprehensive effort. These documents have a fundamental role in orienting the plans and activities of national stakeholders, such as agronomists, researchers, and local and national-level institutions. We analyze and compare the second-generation NAPs (2019–2022) of 10 EU MSs to assess their strengths and weakness and their modifications from the first generation of NAPs (2009). We advance several recommendations on how to make them more valuable instruments in structuring activities towards achieving the goals of the SUD.